Item Analysis for Measuring Student and Academic Advisor’s Perspective towards the Function of Academic Advising in Malaysian Public Universities - Thuy Van, Nguyen; Said, Hamdan; Rustam Mohd Rameli, Mohd; Khan, Aqeel (International Journal of Engineering and Technology, 2018)
In Malaysian public universities, academicians are appointed as academic advisors. This action often leads to misunderstandings on the function of academic advising among students and academic advisors. Previous studies examining this misunderstanding were conducted using standardized instrument. These instruments were developed by researchers from advanced countries where professionals are employed as academic advisors. These standardized instruments lack of local context, differentiatition between academicians and professionals, and statistical properties including individual item quality and ability. This study fills this gap by identifying the rank of each item of the self-developedquestionnaire regarding the function of academic advising from the perspective of student and academic advisor. The questionnaire in this study was developed based on the findings of the preliminary qualitative study. The questionnaire consists of three constructs: academic, social, and personal. A total of 400 students and 80 academic advisors from two public universities ranked each item of the questionnaire based on four-point scales. The questionnaire was analysed using Rasch measurement model. The findings showed that students perceive academic aspect while academic advisors perceive personal development aspect as the most important function of academic advising. Students and academic advisors perceived social aspect as the least important of academic advising. Finally, students perceived personal development aspect while academic advisors considered academic aspect as the second important function of academic advising. The findings could serve as a guideline to improve the quality of academic advising programme in Malaysian public universities.Â